ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA KARYAWAN PT BANK PANIN DUBAI SYARIAH, TBK JABODETABEK SELAMA MASA PANDEMIK COVID-19 - Saragi Sitio, Vera Sylvia (JURNAL ILMIAH M-PROGRESS, 2021)
Environmental changes that are quite significant are experienced by employees as a result of the Covid -19 virus, so that employees are required to be able to carry out their work productively and professionally. The purpose of this study is to identify the factors that affect employee productivity and to analyze the dominance of these factors. The number of samples in this study amounted to 86 respondents using purposive sampling technique. The research method used is Structural Equation Modeling (SEM) with the Smart PLS 3.0 application and path path analysis. The results showed that there was an effect of mental attitude, skills and technology with the coefficient of determination R2 valued at 98.5%. The results of the analysis of dominance show that there are dominant indicators that affect productivity, including the loading factor value for each variable. Mental attitude has a value of 0.956, stability is 0.898 and technology is 0.949Â Keyword : Mental Attitude, Skills, Technology and Productivity